Heart failure drug proscillaridin A targets MYC overexpressing leukemia through global loss of lysine acetylation - Elodie M. Da Costa; Gregory Armaos; Gabrielle McInnes; Annie Beaudry; Gaël Moquin-Beaudry; Virginie Bertrand-Lehouillier; Maxime Caron; Chantal Richer; Pascal St-Onge; Jeffrey R. Johnson; Nevan Krogan; Yuka Sai; et al. (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Cardiac glycosides are approved for the treatment of heart failure as Na+/K+ pump inhibitors. Their repurposing in oncology is currently investigated in preclinical and clinical studies. However, the identification of a specific cancer type defined by a molecular signature to design targeted clinical trials with cardiac glycosides remains to be characterized. Here, we demonstrate that cardiac glycoside proscillaridin A specifically targets MYC overexpressing leukemia cells and leukemia stem cells by causing MYC degradation, epigenetic reprogramming and leukemia differentiation through loss of lysine acetylation. Methods Proscillaridin A anticancer activity was investigated against a panel of human leukemia and solid tumor cell lines with different MYC expression levels, overexpression in vitro systems and leukemia stem cells. RNA-sequencing and differentiation studies were used to characterize transcriptional and phenotypic changes. Drug-induced epigenetic changes were studied by chromatin post-translational modification analysis, expression of chromatin regulators, chromatin immunoprecipitation, and mass-spectrometry. Results At a clinically relevant dose, proscillaridin A rapidly altered MYC protein half-life causing MYC degradation and growth inhibition. Transcriptomic profile of leukemic cells after treatment showed a downregulation of genes involved in MYC pathways, cell replication and an upregulation of hematopoietic differentiation genes. Functional studies confirmed cell cycle inhibition and the onset of leukemia differentiation even after drug removal. Proscillaridin A induced a significant loss of lysine acetylation in histone H3 (at lysine 9, 14, 18 and 27) and in non-histone proteins such as MYC itself, MYC target proteins, and a series of histone acetylation regulators. Global loss of acetylation correlated with the rapid downregulation of histone acetyltransferases. Importantly, proscillaridin A demonstrated anticancer activity against lymphoid and myeloid stem cell populations characterized by MYC overexpression. Conclusion Overall, these results strongly support the repurposing of proscillaridin A in MYC overexpressing leukemia.